Effect of Product Development and Product Quality on Customer Satisfaction in Superior Gelora Light in West Jakarta - Gojali Supiandi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of product development and product quality on consumer satisfaction at PT. Gelora Cahaya Unggul in West Jakarta. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. This study's results show product development significantly affects consumer satisfaction by 40.5%; hypothesis testing is obtained through t count> t table, or (7.996> 1.986). Product quality significantly affects consumer satisfaction by 38.8%; hypothesis testing obtained t count> t table or (7,718> 1,986). Product development and product quality simultaneously have a significant effect on customer satisfaction with the regression equation Y = 10.648 + 0.382X1 + 0.362X2, and the contribution of the effect is 49.7%; the hypothesis test obtained F count> F table or (46.018> 2,700).